Screening for Nutritional Status and Strengthening Healthy Lifestyle in Adolescents: Skrining Status Gizi dan Penguatan Pola Hidup Sehat Remaja - Ulfa, Laila; Adawiyah, Asyifa Robiatul; Lestari, Dini Indah; Samingan, Samingan; Fidzikri, Nanda Berliana Tania (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Lack of awareness among adolescents towards healthy lifestyle has an impact on the risk of non-communicable diseases. The purpose of this community service activity was to improve adolescent knowledge of a healthy lifestyle and screening their nutritional status by measuring their BMI-for-age to prevent the risk of malnutrition (underweight or overweight). Improvement knowledge of healthy lifestyles carried out by providing counseling on nutrition-balanced and physical activity. The results of the activity showed an increase in the mean of knowledge score from 9.95(±SD1,29) to 11.57(±SD2,12). BMI measurements showed that the majority of adolescents (62%) had normal nutritional status, 21% were overnourished, 11.6% were obese, and 4.2% were undernourished. Counseling on nutrition-balanced and physical activity could increase healthy lifestyle knowledge for adolescence, and there is a tendency for adolescence to lead a problem with overnutrition. Therefore, sustainable youth education program required to provide a healthy lifestyle.